Influence of timing of Levosimendan administration on outcomes in cardiac surgery - Schiefenhövel, Fridtjof; Berger, Christian; Penkova, Liubov; Grubitzsch, Herko; Haller, Bernhard; Meyer, Alexander; Heringlake, Matthias; Sander, Michael; Erb, Joachim M.; Balzer, Felix; Treskatsch, Sascha (Frontiers in Cardiovascular Medicine, 2023)
Purpose: Though a subgroup analysis has shown improved survival for patients suffering severely reduced ventricular function undergoing coronary artery bypass grafting, RCTs were not able to demonstrate overall beneficial effects of perioperative Levosimendan in cardiac surgery. This might be due to Levosimendan´s pharmacokinetics reaching a steady-state concentration only 4 to 8 hours after administration. Thus, this study now analysed the influence of timing of Levosimendan administration on perioperative outcome in cardiac surgery patients preoperatively presenting with severely reduced ventricular function and therefore considered at high-risk for intra-or postoperative low cardiac output syndrome. We hypothesized that prolonged preoperative Levosimendan administration ("preconditioning") would reduce mortality.Methods: All adult patients undergoing cardiac surgery between 2006 and 2018 perioperatively receiving Levosimendan were included in this retrospective, observational cohort study (n=498). Patients were stratified into 3 groups: Levosimendan started on the day prior to surgery ("preop"), Levosimendan started on the day of surgery ("intraop") or post ICU admission ("postop"). After propensity score matching (PSM) was performed, outcomes defined according to proposed standard definitions for perioperative outcome research were compared between groups.Results: After PSM, there were no significant differences in patients´ characteristics, comorbidities and type/priority of surgery between groups. Compared to intraop or postop Levosimendan treatment, preop treated patients had significantly lower in-hospital-mortality (preop vs. intraop. vs. postop = 16,7 % vs. 33,3 % vs. 42,3 %), duration of mechanical ventilation and rate of continuous renal replacement therapy.